Developments in natural rubber biotechnologies compared to other major tropical crops in a globalization context - Montoro P (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.73-88.)
It is considered that biotechnologies will play a leading role in the near future in improving productivity and resistance to diseases and insects for a wide variety of plant species. In order to assess the potential for developing rubber tree biotechnologies, knowledge and the availability of advanced techniques acquired over the last thirty years are compared to those obtained for other tree crops of major importance for the agroindustry in tropical and subtropical countries, such as coconut, cocoa, coffee or oil palm. National and international research initiatives play a decisive role in the innovation process. In a more general sense, the applications of genetic engineering are an unprecedented economic challenge with a major impact on the R & D industry, changes in cultural practices and ecology. Improving links between those involed in biotechnology research, and between them and stakeholders in the natural rubber commodity chain, is a factor for the success of future applications.
Keywords: Agribusiness; Globalization